Adenocarcinoma cervical in situ: fatores relacionados com a presença de lesão residual após conização - Santos,Joana Almeida (2017)
Overview and Aims: The currently accepted treatment for cervical adenocarcinoma in situ is total hysterectomy. However, considering this is a condition that frequently affects young women, the safety of a conservative treatment in selected cases is under investigation. This study aimed to evaluate the factors possibly associated with the presence of residual lesion in patients undergoing conization for adenocarcinoma in situ of the cervix. Study Design: Retrospective observational study. Population and Methods: Analysis of factors possibly associated with the presence of residual tumor in 72 patients submitted to conization for adenocarcinoma in situ of the cervix from January 1993 to December 2012. Results: Forty-six of the 72 patients were included in the analysis. In 19 cases (41%) involvement of conization margins was confirmed; the endocervical study was conducted on 37 cases (80.4%) and revealed adenocarcinoma in situ in 7 cases (18.9%). When analyzed separately, the positive predictive value of the endocervical study was higher than the involvement of conization margins (85.7% vs 52.6%). When both factors were combined, it was found that when both were negative, no residual tumor was identified; positivity of both corresponded, in all cases, to the presence of residual lesion. Statistically significant difference was found between the two groups (with and without residual AIS) regarding margin involvement and the endocervical study (p < 0,05). Conclusion: This study confirms and reinforces the idea that a conservative approach can be considered in selected cases of patients wishing to preserve fertility, considering the margins of cone biopsy and the endocervical study are both negative. However, these patients should be maintained in surveillance and a definitive treatment should be recommended after completion of the reproductive project.